Geochemistry of Granites in Panggong Lalat, Gua Musang, Kelantan - Shafiee Nor Shahida; Mohd Yusri Muhammad Afif Aflah; Achmad Bahar Arham Muchtar; Sulaiman Noorzamzarina (BIO Web of Conferences)
Granites are among the most significant rock formations in the Earth’s crust and play a crucial role in various geological processes. This study focuses on examining the geology and granitic rock formations in Panggong Lalat, Gua Musang, Kelantan through field surveys, geological mapping, and geochemical analysis for better understand the geological framework and characteristics of granite in this area. The findings indicate that the lithology of the study area includes granitoids, well-bedded limestone, volcanic rocks, fine-grained sediments, and meta-sedimentary rocks. Petrographic analysis of five samples identified three granitoid types: quartz-rich granitoid, quartz alkali feldspar syenite, and alkali feldspar granite, classified using the IUGS scheme. The X-ray Fluorescence (XRF) data reveals that both samples exhibit typical felsic granite compositions, with high SiO₂ contents in AF 01 (61.61%) and 60.72% in AF02. However, AF 02 displays higher concentrations of TiO₂, FeO, and MnO, suggesting a greater contribution of mafic minerals compared to AF 01. Additionally, CaO content is slightly higher in AF02, indicating a more significant presence of plagioclase feldspar, while AF01 is enriched in K₂O. The Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES) data further reinforce the distinction between AF 01 and AF 02. Both samples are enriched in Rare Earth Elements (REE), particularly Ce, Er, and La. A F02 shows significantly higher concentrations of Ce (213.85 ppm) and Er (7554.11 ppm) compared to AF 01 (166.12 ppm for Ce and 3047.54 ppm for Er), indicating a stronger REE enrichment in AF 02.The distribution of Heavy Rare Earth Elements (HREE) is more abundant than that of Light Rare Earth Elements (LREE), with Er exhibiting the highest concentration and Nd the lowest.